Wireless capsule endoscopy versus ileocolonoscopy for the diagnosis of postoperative recurrence of Crohn's disease: a prospective study. Issue 7 (9th January 2006) - Bourreille, A; Jarry, M; D'Halluin, P N; Ben-Soussan, E; Maunoury, V; Bulois, P; Sacher-Huvelin, S; Vahedy, K; Lerebours, E; Heresbach, D; Bretagne, J F; Colombel, J F; et al.
Abstract : Background and aims: Following ileocolonic resection for Crohn's disease (CD), early endoscopic recurrence predicts recurrence of symptoms. The aim of the study was to compare ileocolonoscopy and wireless capsule endoscopy (WCE) for the detection of postoperative recurrence in CD. Methods: WCE and ileocolonoscopy were performed within six months following surgery in 32 prospectively enrolled patients. Two independent observers interpreted the results of WCE. Recurrence in the neoterminal ileum was defined by a Rutgeerts score ⩾1. When observers at WCE did not concur, WCE results were considered as either true negative or true positive and sensitivity and specificity were calculated according to both assumptions. Results: Recurrence occurred in 21 patients (68%) and was detected by ileocolonoscopy in 19 patients. Sensitivity was 90% and specificity 100%. Sensitivity of WCE was 62% and 76% and specificity was 100% and 90%, respectively, depending on assumptions. There was a correlation between the severity of the lesions measured by both methods (p<0.05). Lesions located outside the scope of conventional endoscopy were detected by WCE in two thirds of patients with excellent interobserver agreement (kappa >0.9) for all lesions with the exception of ulceration (kappa = 0.7). Conclusions: The sensitivity of WCE in detecting recurrence in the neoterminal ileum was inferior to that of ileocolonoscopy. In contrast, WCE detected lesions outside the scope of ileocolonoscopy in more than two thirds of patients. Additional follow up studies are needed to assess the clinical relevance of such lesions. At the present time, it seems that WCE cannot systematically replace ileocolonoscopy in the regular management of patients after surgery.